-22x+12y=66

Simple and best practice solution for -22x+12y=66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -22x+12y=66 equation:


Simplifying
-22x + 12y = 66

Solving
-22x + 12y = 66

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12y' to each side of the equation.
-22x + 12y + -12y = 66 + -12y

Combine like terms: 12y + -12y = 0
-22x + 0 = 66 + -12y
-22x = 66 + -12y

Divide each side by '-22'.
x = -3 + 0.5454545455y

Simplifying
x = -3 + 0.5454545455y

See similar equations:

| .60x+0.05(60)=0.30(90) | | -4b+2b=10-16 | | x+20+4x=-4x-25 | | 3x=9y+9 | | 5(2b+3)=2b+a | | (x^2-16)/(x-2) | | 2cos^2+3cos=2 | | x^2-18x-1=-6 | | 8+4X-9+5=16 | | 1v/1i=r | | 12-(3m+7)=4+2m-19 | | 9t-4(5t+t)=8t-3 | | 24x-3y=-12 | | 10+3n=37 | | 3(x+1)+3x+3=42 | | 2x-2=1x+64 | | hb-qb=5f^2 | | 2/3-?=1 | | -2(4-2x)+3x=2x+2(5+x)-6 | | -2(4-2x)+3x=2x+(5+x)-6 | | -2(2-2x)+3x=2x+(5+x)-6 | | p+10=4Q | | (8/y)÷(24/y) | | 6/v-3 | | 21/1=x/18 | | (-x^2)-5x+1=0 | | -10p+7=-183 | | 17-3b=4b+87 | | 8m-9=-24m+55 | | (-6)+(-4)= | | 120=12x-24 | | x+5x+2x+4+7=7-8 |

Equations solver categories